Providing bereavement care to families of deceased children at the University Hospital Motol (Paliativní medicína, 2024)
Introduction: The standard of pediatric palliative care in developed countries is the provision of professional support to the bereaved families of deceased pediatric patients. Bereavement care is usually provided by the hospital palliative care team. As part of the rapid development of pediatric palliative care in the Czech Republic, efforts are taken to anchor bereavement care in the health service delivery system. The aim of the study was to assess the provision of bereavement care by the peadiatric support team at the University Hospital in Motol.Methods: We performed a retrospective analysis of data from the electronic medical documentation system and from the database of the Pediatric Supportive Care Team of the Motol Hospital from 1 January 2021 to 31 December 2023. The main purpose of the analysis was to evaluate the number of interventions performed, the time required and the types of professions involved in providing care for the survivors of a deceased child.Results: The majority of interventions were performed by bereavement therapists (N=217, 30%) and team physicians (N=207, 29%). The time allocated to bereavement care had an increasing trend, with 120, 164 and 220 hours per year in 2021, 2022 and 2023, respectively.Conclusion: Bereavement care in Motol Hospital is provided by bereavement therapists and other professions of the team. Professional support for the bereaved is showing a long-term increasing trend. Further research is needed to assess acute stabilization interventions by the crisis interventionists and other support professions involved in bereavement care.
Keywords: bereavement care; bereavement therapist; deceased child; pediatric palliative care